Multicomponent reactions in organic synthesis - Zhu, Jieping; Wang, Qian (Research scientist); Wang, Mei-Xiang (Wiley, 2015)
Comprehensive and up-to-date, this book focuses on the latest advances in the field, such as newly developed techniques, more environmentally benign processes, broadened scopes, and completely novel MCRs. In addition to carbene-promoted MCRs and frequently applied metal-catalyzed MCRs, it also covers recently developed catalytic enantioselective variants as well as MCR in drug discovery and for the synthesis of heterocyclic molecules and macrocycles. Edited by the leading experts and with a list of authors reading like a ""who's who"" in multicomponent reaction chemistry, this is definitely a